Therapeutic Potential of Targeting the SUMO Pathway in Cancer - Kukkula Antti; Ojala Veera K.; Mendez Lourdes M; Sistonen Lea; Elenius Klaus; Sundvall Maria (MDPI, 2025)
The small ubiquitin-like modifier (SUMO) pathway regulates the hallmark properties of cancer cells. Moreover, alterations in activity and in levels of SUMO machinery components have been observed in human cancer. Due to the reversible nature of this post-translational protein modification, the balance between SUMOylation and the removal of SUMO is critical. Early-phase clinical trials are currently evaluating the safety and efficacy of SUMO pathway inhibition in cancer patients. In this comprehensive review, we critically discuss the potential of targeting the SUMO pathway as a therapeutic option for cancer.